Answer:
2 is added
Step-by-step explanation:
Answer:
5 11/13km
Step-by-step explanation:
4 ( 1 6/13)
4× 19/13
= 5 11/13
3x^2 - 12 = 0
Personally, I would divide each side by 3 x^2 - 4 = 0
Then I would add 4 to each side x^2 = 4
Then I would take the square root of each side: x = +4
x = -4 .
Having found both solutions, I would relax with a cup of tea.
The distributive property: a(b + c) = ab + ac
(x - 3)(4x + 2) = (x)(4x + 2) + (-3)(4x + 2)
= (x)(4x) + (x)(2) + (-3)(4x) + (-3)(2) = 4x² + 2x - 12x - 6
<h3>= 4x² - 10x - 6</h3>